Samosprožena stimulirana emisija - Krušič, Špela (Matrika, 2016)
Under specific conditions the transition of a light pulse through dense gas can lead to strong stimulated emission of light, which is triggered by a completely random spontaneous decay of excited atomic states. Here I present a theoretical treatment of the problem and describe numerical simulations and results for a special case of excited atomic states in helium atoms.
Keywords: atomic physics; atomska fizika; samosprožena stimulirana emisija; self-amplified stimulated emission; stimulated emission; stimulirana emisija